2019
DOI: 10.1029/2019jd030561
|View full text |Cite
|
Sign up to set email alerts
|

Midlatitude Lightning NOx Production Efficiency Inferred From OMI and WWLLN Data

Abstract: Oxides of nitrogen are critical trace gases in the troposphere and are precursors for nitrate aerosol and ozone, which is an important pollutant and greenhouse gas. Lightning is the major source of NOx (NO + NO2) in the middle to upper troposphere. We estimate the production efficiency (PE) of lightning NOx (LNOx) using satellite data from the Ozone Monitoring Instrument and the ground‐based World Wide Lightning Location Network in three northern midlatitudes, primarily continental regions that include much of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 169 publications
(284 reference statements)
13
73
1
Order By: Relevance
“…To test the sensitivity of our results to this stroke rate threshold, we repeated our full analysis at minimum stroke rates spanning 1–10,000 strokes·cell −1 ·hr −1 (Figure a). In agreement with Bucsela et al (), we observed a decreasing trend in LNO 2 with increasing stroke frequency that was accompanied by an increasing trend in R 2 . For example, increasing the minimum stroke rate to 5,000 strokes·cell −1 ·hr −1 decreased total LNO 2 by 13% and increased R 2 to 0.6 (from 0.54).…”
Section: Deriving Lno2supporting
confidence: 93%
See 4 more Smart Citations
“…To test the sensitivity of our results to this stroke rate threshold, we repeated our full analysis at minimum stroke rates spanning 1–10,000 strokes·cell −1 ·hr −1 (Figure a). In agreement with Bucsela et al (), we observed a decreasing trend in LNO 2 with increasing stroke frequency that was accompanied by an increasing trend in R 2 . For example, increasing the minimum stroke rate to 5,000 strokes·cell −1 ·hr −1 decreased total LNO 2 by 13% and increased R 2 to 0.6 (from 0.54).…”
Section: Deriving Lno2supporting
confidence: 93%
“…At a higher minimum stroke rate of 10,000 strokes·cell −1 ·hr −1 , total LNO 2 decreased by 31%, and R 2 increased to 0.66. As a consequence of focusing on higher stroke rate storms, our absolute LNO 2 production efficiencies yielded lower LNO 2 per flash compared to those that would be derived using a lower threshold and should be interpreted in the context of the LNO x dependence on stroke frequency (Bucsela et al, ). Critical to this work, we also observed a dependence on minimum stroke rate for the CG/IC LNO 2 , which was largely caused by variability in CG LNO 2 (Figure ), which we report in section and discuss in section .…”
Section: Deriving Lno2mentioning
confidence: 68%
See 3 more Smart Citations